Pengaruh suplementasi sinbiotik berbasis inulin bengkoang, transplantasi mikroba dari EM4 dan fermentasi kulit nanas terhadap produktivitas ayam broiler - Rinawidiastuti; Roisu Eny Mudawaroch; Uswatun Hasanah (Fakultas Pertanian Universitas Majalengka, 2026)
This study aimed to evaluate the effect of a synbiotic powder based on yam inulin, microba transplant from EM4 and fermented pineapple peel on the productivity of broiler chickens. The research carried out experimentally and used a completely randomised design with five treatments and four replications: P0 (100% commercial feed as control), P1 (feed + 5% synbiotic powder), P2 (feed + 10% synbiotic powder), P3 (feed + 15% synbiotic powder), and P4 (feed + 20% synbiotic powder). Parameters observed were feed intake, water intake, weight gain, FCR, and feed efficiency. The results showed that synbiotic powder significantly affected feed intake, FCR, and feed efficiency (P<0.05), while other parameters showed no significant difference. The best FCR and feed efficiency were observed in treatment P4. Thus, synbiotic powder can be added up to 20% in broiler rations to improve feed efficiency without reducing performance.